Photocatalyst for degrading tetracycline and preparation method thereof

By preparing ZnSnO3/Ag2WO4 composite photocatalyst, the heterojunction structure is used to improve the photocatalytic activity, and the problem of low efficiency of existing photocatalysts when degrading tetracycline is solved, achieving efficient and stable tetracycline degradation effect.

CN119565605AActive Publication Date: 2025-03-07HEBEI UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411695544.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing photocatalysts have low efficiency when degrading tetracycline, have a wide band gap, long response time to light, and have high regeneration costs, which limits their effectiveness in practical applications.

Method used

ZnSnO3/Ag2WO4 composite photocatalyst was prepared by hydrothermal method and calcination method, and the photocatalytic activity was improved by using heterojunction structure.

Benefits of technology

Highly efficient degradation of tetracycline was achieved, the reaction rate was significantly improved, the photocatalytic activity was much higher than that of pure ZnSnO3 and Ag2WO4, and it showed good stability and reusability under visible light irradiation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565605A_ABST
    Figure CN119565605A_ABST
Patent Text Reader

Abstract

The invention relates to a photocatalyst for degrading tetracycline and a preparation method thereof. The preparation method comprises the following steps: dissolving SnCl45H2O and NaOH in deionized water, uniformly stirring, adjusting the pH value of the solution, heating to 60 DEG C, adding ZnSO47H2O, and keeping at the temperature of 60 DEG C for at least 8 hours; and centrifugally separating the reactant to obtain a solid product, washing the solid product with deionized water, drying the solid product at 60 DEG C for 12 hours, taking out the solid product, and calcining the solid product at 580 DEG C for 2 hours to obtain ZnSnO3. Then adding Na2WO4H2O and ZnSnO3 into deionized water, and stirring, so as to obtain a solution A; agNO3 is dissolved in deionized water according to the molar ratio of 2: 1, and a solution B is obtained; and adding the solution B into the solution A, uniformly stirring, taking out a solid product obtained by reaction, washing, drying, and calcining at the temperature of 400 DEG C for 2 hours to obtain the photocatalyst ZnSnO3 / Ag2WO4. The invention provides a new thought for designing a high-efficiency photocatalyst applied to environmental restoration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a photocatalyst, in particular to a photocatalyst for degrading tetracycline and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of the pharmaceutical industry, the use of antibiotics has increased significantly. Antibiotics enter the water environment through various pathways such as pharmaceutical industrial wastewater, livestock breeding wastewater, and medical industry wastewater. Tetracycline is a widely used antibiotic that can be used to treat a variety of bacterial infections. However, residual antibiotics in the environment can enter surface water, groundwater, and even drinking water through surface runoff and leaching, leading to a series of water pollution problems and posing a serious threat to human health.

[0003] People have gradually developed methods to treat wastewater containing tetracycline. Currently, the methods for removing tetracycline from water bodies generally include physical adsorption, biodegradation, ozone oxidation, and photocatalytic oxidation. Among them, photocatalytic oxidation is a pollutant degradation technology that uses semiconductors as catalysts and uses solar energy to decompose organic matter. It has a good degradation effect on antibiotics. Currently known photocatalysts include TiO 2 , ZnO and In 2 O 3 However, these traditional photocatalysts have wide band gaps, long light response times, low photocatalytic efficiency and high regeneration costs, which limit their practical applications.

[0004] ZnSnO 3 As a multifunctional material, it has been widely used in photocatalysis, gas sensing, solar cells and other fields due to its high electronic conductivity, excellent optical properties, high stability, low cost, and non-toxicity. 3 The absorption capacity of visible light is poor, the electron and hole recombination speed is fast, and the band gap is wide, so ZnSnO 3 The photocatalytic activity is still unsatisfactory, which limits its application in the field of optical photocatalysis.

[0005] Generally, for wide bandgap photocatalysts, coupling them with narrow bandgap photocatalysts whose ECB is higher than that of the wide bandgap photocatalyst to construct a heterojunction is an effective way to overcome the above shortcomings.

[0006] Ag 2 WO 4It is widely used in many important fields, such as electronics, catalysis, environmental protection and electrode materials. It has good photocatalytic activity against pollutants under visible light irradiation. However, its application is seriously affected by its limited visible light collection capacity and photocorrosion. However, to a certain extent, these shortcomings can be overcome by constructing composite photocatalysts. Summary of the invention

[0007] The purpose of the present invention is to provide a photocatalyst for degrading tetracycline and a preparation method thereof, so as to solve the problem of antibiotic pollution caused by the use of tetracycline.

[0008] The object of the present invention is achieved in that:

[0009] A method for preparing a photocatalyst for degrading tetracycline comprises the following steps:

[0010] S1, ZnSnO 3 Synthesis: SnCl 4 ·5H 2 O and NaOH were dissolved in deionized water, stirred evenly, the pH of the solution was adjusted to 11.3, heated to 60 °C, and ZnSO 4 7H 2 O, kept at 60℃ for at least 8h; the reactant was separated by centrifugation to obtain a solid product, which was washed with deionized water, dried at 60℃ for 12h, taken out and calcined at 580℃ for 2h to obtain ZnSnO 3 .

[0011] Synthesis of S2 and ZA-2: Na 2 WO 4 ·H 2 O and ZnSnO 3 Add to deionized water and stir to obtain solution A; add AgNO 3 Dissolve in deionized water at a molar ratio of 2:1 to obtain solution B; add solution B to solution A and stir evenly; take out the solid product obtained by the reaction, wash and dry it, and calcine it at 400°C for 2h to obtain the photocatalyst ZnSnO 3 / Ag 2 WO 4 , called ZA-2.

[0012] Furthermore, the material ratio in step S1 is:

[0013]

[0014] Furthermore, the material ratio in step S2 is:

[0015] Na 2 WO 4 ·H2 O ZnSnO 3 Deionized water

[0016] 0.20g 0.56g 80mL.

[0017] Furthermore, the preparation method of the present invention converts the Na in step S2 into 2 WO 4 ·H 2 The amount of O added increased by 50%, and the photocatalyst ZnSnO 3 / Ag 2 WO 4 Called ZA-1.

[0018] Furthermore, the preparation method of the present invention converts the Na in step S2 into 2 WO 4 ·H 2 The amount of O added was reduced by 50%, and the photocatalyst ZnSnO 3 / Ag 2 WO 4 Called ZA-3.

[0019] The purpose of the present invention can also be achieved like this:

[0020] A photocatalyst for degrading tetracycline is prepared by adopting the preparation method of the photocatalyst of the invention.

[0021] The present invention prepares a new type of ZnSnO 3 / Ag 2 WO 4 Photocatalyst. The photocatalyst ZnSnO was successfully prepared by hydrothermal method and calcination method. 3 / Ag 2 WO 4 The SEM and TEM images show that ZnSnO 3 and Ag 2 WO 4 The ZnSnO 3 / Ag 2 WO 4 The chemical state and optical properties of the photocatalyst. In addition, the transient photocurrent response, EIS Nyquist spectrum and Mott-Schottky spectrum of ZnSnO were studied. 3 / Ag 2 WO 4 The results show that ZnSnO 3 / Ag 2 WO 4The composite material has excellent photocarrier generation and transport capabilities, and its photocatalytic activity is much higher than that of pure ZnSnO 3 and Ag 2 WO 4 In addition, photocatalytic degradation experiments showed that under visible light irradiation, ZnSnO 3 / Ag 2 WO 4 The composite material has the best degradation effect on tetracycline and the highest reaction rate.

[0022] The present invention prepares a new type of ZnSnO 3 / Ag 2 WO 4 Heterojunction photocatalysts prove the existence of interfacial chemical bonds, maximize the advantages of photocatalysts, improve the response to visible light, reveal the mechanism of photogenerated charge migration, and achieve effective separation of photogenerated carriers.

[0023] The present invention provides a new idea for designing high-efficiency photocatalysts for environmental restoration. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The photocatalyst ZnSnO of the present invention 3 / Ag 2 WO 4 Preparation process flow chart.

[0025] Figure 2 The electron microscope images, micrographs and elemental mapping images of the photocatalyst and its related products; (a) is ZnSnO 3 SEM micrograph of Ag 2 WO 4 SEM micrograph of ZnSnO 3 / Ag 2 WO 4 SEM micrograph of ZnSnO 3 HRTEM micrograph of Ag 2 WO 4 HRTEM micrograph of ZnSnO 3 / Ag 2 WO 4 HRTEM micrographs; (g)-(l) are ZnSnO 3 / Ag 2 WO 4 Elemental mapping of Zn, Sn, O, Ag, and W in MgO.

[0026] Figure 3 ZnSnO 3 、Ag2 WO 4 and ZnSnO 3 / Ag 2 WO 4 XRD pattern of .

[0027] Figure 4 ZnSnO 3 、Ag 2 WO 4 and ZnSnO 3 / Ag 2 WO 4 Optical characterization diagram; wherein, (a) is the nitrogen adsorption-desorption isotherm diagram; (b) is the pore size distribution diagram of the adsorption branch of the isotherm calculated using the Barrett-Joyner-Halenda method.

[0028] Figure 5 ZnSnO 3 / Ag 2 WO 4 XPS spectra; where (a) is survey, (b) is Zn 2p, (c) is Sn 3d, (d) is O1s, (e) is Ag 3d, and (f) is W 4f.

[0029] Figure 6 ZnSnO 3 、Ag 2 WO 4 and ZnSnO 3 / Ag 2 WO 4 Electrochemical characterization diagram; among them, (a) is the electrochemical impedance diagram; (b) is the transient photocurrent response diagram; (c) is the Mott-Schottky diagram; (d) is the PL spectrum.

[0030] Figure 7 is the photocatalytic degradation diagram of tetracycline under visible light irradiation; where (a) is the photocatalytic degradation diagram of tetracycline under visible light irradiation; 3 、Ag 2 WO 4 and ZnSnO 3 / Ag 2 WO 4 Schematic diagram of the degradation of tetracycline in the presence of ZnSnO 3 、Ag 2 WO 4 and ZnSnO 3 / Ag 2 WO 4 (c) is a schematic diagram of the first-order degradation kinetics of tetracycline under the presence of ZnSnO; (c) is a schematic diagram of the photocatalytic degradation of tetracycline under visible light, showing that ZnSnO 3 / Ag2 WO 4 Changes in photocatalytic activity over three consecutive usage cycles. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.

[0032] like Figure 1 As shown, the preparation method of the photocatalyst of the present invention comprises the following steps:

[0033] S1, ZnSnO 3 Synthesis: 0.32 g SnCl 4 ·5H 2 O and 0.14 g NaOH were dissolved in 40 mL deionized water and stirred. The pH of the solution was adjusted to 11.3, heated to 60 °C, and 0.26 g ZnSO 4 7H 2 O, kept at 60°C overnight. The solid product was obtained by centrifugation, washed with deionized water, dried in an oven at 60°C for 12h, and then calcined at 580°C for 2h to obtain ZnSnO 3 .

[0034] Synthesis of S2 and ZA-2: 0.20 g Na 2 WO 4 ·H 2 O and 0.56g ZnSnO 3 Add to 80 mL of deionized water and stir for 15 min to obtain solution A. 3 (AgNO 3 with Na 2 WO 4 ·H 2 O with a molar ratio of 2:1) was dissolved in 80 mL of deionized water to obtain solution B; solution B was added to solution A and stirred for 2 h, and the obtained solid product was washed, dried, and calcined at 400 °C for 2 h to obtain the photocatalyst ZnSnO 3 / Ag 2 WO 4 , called ZA-2.

[0035] In the preparation method of the present invention, if the Na 2 WO 4 ·H 2 The amount of O added was changed to 0.30 g, and the photocatalyst ZnSnO 3 / Ag 2 WO 4 , called ZA-1.

[0036] In the preparation method of the present invention, if the Na 2 WO 4 ·The amount of H2O added was changed to 0.10g, and the photocatalyst ZnSnO generated by the reaction 3 / Ag 2 WO 4 , called ZA-3.

[0037] Photocatalyst ZnSnO of the present invention 3 / Ag 2 WO 4 Characterization:

[0038] Photocatalyst ZnSnO obtained using scanning electron microscopy 3 / Ag 2 WO 4 The morphological information and microstructure of the composites were obtained. The lattice information of the composites was observed by transmission electron microscopy. The crystal structure of the samples was determined using X-ray diffraction analysis. The BET specific surface area and its corresponding pore size distribution were determined using an automatic BET analyzer. X-ray photoelectron spectroscopy was used to analyze the chemical composition and surface state of the samples. The photoluminescence properties were studied using a fluorescence spectrophotometer.

[0039] Photocatalyst ZnSnO of the present invention 3 / Ag 2 WO 4 Photocatalytic experiment:

[0040] With tetracycline as a model pollutant, photocatalytic experiments were carried out in a PL-X300D-FH photochemical reactor to evaluate the photocatalytic activity of the photocatalyst. The light source was provided by a 300W xenon lamp and a UV filter (wavelength <420nm). 100mg of the catalyst was evenly dispersed in 100ml of tetracycline solution (20mg / L) and placed in a jacketed beaker connected to a circulating water system. Before illumination, the mixed solution was stirred on a magnetic stirrer at 500rpm / min for 30min under dark conditions to reach adsorption-desorption equilibrium. Subsequently, about 2mL of the suspension was extracted using a 2mL plastic syringe at 0min, 2min, 5min, 10min, and 15min, respectively, and the catalyst particles were filtered through a 0.22μm membrane filter. The concentration of tetracycline can be determined by high performance liquid chromatography. The detection method is, A acetonitrile (15%), B 2% formic acid solution (85%), temperature is 40℃, flow rate is 1mL / min. The detection wavelength is 275nm.

[0041] The morphology and microstructure of the photocatalyst prepared by the present invention are as follows: Figure 2 SEM was used to observe the ZnSnO 3 、Ag 2 WO 4And the photocatalyst ZnSnO of the present invention 3 / Ag 2 WO 4 Microstructure of pure ZnSnO 3 The SEM images are as follows Figure 2 As shown in (a), it is composed of irregular blocky particles. Figure 2 (b) shows Ag 2 WO 4 The structure is rod-like, which is consistent with previous reports. Figure 2 (c) ZnSnO 3 / Ag 2 WO 4 From the SEM images, we can see that the ZnSnO 3 The bulk and corresponding to Ag 2 WO 4 rod-shaped, indicating that there is ZnSnO in the composite material 3 and Ag 2 WO 4 .like Figure 2 (d)— Figure 2 As shown in (l), ZnSnO 3 、Ag 2 WO 4 and ZnSnO 3 / Ag 2 WO 4 TEM and HRTEM were used to further confirm that ZnSnO 3 / Ag 2 WO 4 Construction of composite materials. TEM images are shown in Figure 2 (d)— Figure 2 As shown in (e), ZnSnO 3 and Ag 2 WO 4 The close interface contact between them is conducive to effective charge transfer. The adjacent 0.26nm and 0.48nm lattice fringes in the HRTEM image are respectively attributed to ZnSnO 3 The (110) crystal plane and Ag 2 WO 4 The (111) crystal plane of ZnSnO 3 and Ag 2 WO 4 The close combination between them intuitively proves that the construction of heterojunction can lead to the recombination of semiconductors and produce a synergistic effect. Figure 2 (g)— Figure 2 (l) shows that ZnSnO 3 / Ag 2 WO 4Elemental mapping of the composite material confirms the presence of Zn, Sn, O, Ag and W in the ZnSnO 3 / Ag 2 WO 4 Uniform distribution in composite materials.

[0042] XRD further verified that pure ZnSnO 3 、Ag 2 WO 4 and ZnSnO 3 / Ag 2 WO 4 The crystal structure of Figure 3 As shown in the figure, the diffraction peaks of all samples are relatively clear, indicating that the crystallinity of all samples is high. 3 All diffraction peaks of the material are consistent with well-crystallized ZnSnO 3 The characteristic peaks of pure ZnSnO are very consistent (JCPDS No.01-089-0095). 3 The diffraction characteristic peaks centered at 32.0°, 33.9°, 37.4°, and 52.1° can correspond to the hexagonal ZnSnO 3 The (104), (110), (015) and (11-6) crystal planes of the prepared pure Ag 2 WO 4 The sample has eight diffraction peaks at 30.2°, 31.5°, 32.8°, 45.2°, 54.4°, 55.3°, 57.0°, and 57.9°, corresponding to orthorhombic Ag. 2 WO 4 (JCPDS No.70-1719) with (002), (231), (400), (060), (233), (352), (550) and (631) crystal planes. 3 / Ag 2 WO 4 The diffraction peaks can be well attributed to ZnSnO 3 and Ag 2 WO 4 , indicating that Ag 2 WO 4 Has been successfully introduced into ZnSnO 3 Ag 2 WO 4 The peak intensity increases with the amount of Na 2 WO 4 and AgNO 3 In ZnSnO 3 / Ag 2 WO 4In the XRD spectrum of the composite material, except for ZnSnO 3 , and Ag 2 WO 4 There are no other peaks, indicating that ZnSnO 3 / Ag 2 WO 4 The material was successfully synthesized.

[0043] The present invention uses nitrogen adsorption-desorption isotherm to study the ZnSnO 3 、Ag 2 WO 4 and ZnSnO 3 / Ag 2 WO 4 BET specific surface area and pore size. Figure 4 (a) and Figure 4 As shown in (b), ZnSnO 3 、Ag 2 WO 4 and ZnSnO 3 / Ag 2 WO 4 All of them show type IV curves, which conform to the IUPAC classification standard for mesoporous structures. 3 、Ag 2 WO 4 and ZnSnO 3 / Ag 2 WO 4 The BET specific surface areas are 31.86 m 2 / g, 5.96m 2 / g and 40.36m 2 / g, and the corresponding pore volumes are 0.055cm 3 / g, 0.011cm 3 / g and 0.069cm 3 / g. The corresponding pore sizes are 4.34nm, 8.21nm and 5.12nm respectively. ZnSnO 3 / Ag 2 WO 4 The specific surface area and pore volume are larger than those of ZnSnO 3 and Ag 2 WO 4 , which gives ZnSnO 3 / Ag 2 WO 4 More active sites for adsorption and photocatalytic degradation of tetracycline.

[0044] The present invention uses XPS spectrum to study ZnSnO 3 / Ag 2 WO 4The surface composition and chemical state of the composite material. The survey spectrum shows that ZnSnO 3 / Ag 2 WO 4 The presence of Zn, Sn, O, Ag, and W peaks in the composite further supports the ZnSnO 3 / Ag 2 WO 4 Composite material formation. With ZnSnO 3 Compared with ZnSnO 3 / Ag 2 WO 4 The Zn 2p peak in the composite material shows a blue shift. 3 Compared with the Sn 3d peak in ZnSnO 3 / Ag 2 WO 4 The two characteristic peaks of Sn 3d at 495.25eV and 486.85eV in the composite material shifted to the direction of lower binding energy, which can be attributed to the electron acquisition of Zn and Sn atoms after the heterojunction between Zn and Sn was formed at the interface. The formation of OVs inhibited the recombination of electrons and holes and improved the photocatalytic performance.

[0045] like Figure 5 As shown in a, ZnSnO 3 / Ag 2 WO 4 The lattice oxygen, OVs and surface adsorbed oxygen in the O1s spectrum appear at 530.71eV, 531.97eV and 532.91eV, respectively, which is consistent with the ZnSnO 3 and Ag 2 WO 4 Compared with Ag 2 WO 4 Compared with ZnSnO 3 / Ag 2 WO 4 The Ag 3d peak in the composite material shows an obvious blue shift, which may be due to the increase in the electron density of Ag atoms after the Ag-O bond forms a heterojunction at the interface. 3 and Ag 2 WO 4 Compared with ZnSnO 3 / Ag 2 WO 4 The binding energies of Zn 2p, Sn 3d, and Ag 3d of the composite material are slightly shifted downward. It can be inferred that OVs weakened the metallic bonds, resulting in a decrease in the electron density around O and an increase in the electron density around Zn, Sn, and Ag. ZnSnO 3 Zn and Sn atoms in Ag2 WO 4 The O atoms in AgI form bonds with Ag 2 WO 4 The two main peaks of W 4f at 37.66eV and 35.51eV indicate that W exists in the form of W(VI) in ZnSnO 3 / Ag 2 WO 4 In composite materials.

[0046] In order to obtain the relevant information about ZnSnO 3 / Ag 2 WO 4 To get more information about the transition behavior and charge separation of the heterostructure, some photoelectrochemical measurements were performed. Information about the electron transport capacity of the sample can be provided by EIS. At the same time, the changes in EIS are related to the interfacial properties of the material. The presence of a built-in electric field facilitates the migration and separation of photogenerated charges at the interface, and one of the visual manifestations of this phenomenon is a decrease in impedance.

[0047] Figure 6 It is shown that ZnSnO 3 / Ag 2 WO 4 Separation and recombination of photogenerated electrons and holes in composite materials. Figure 6 (a) shows that compared with pure ZnSnO 3 and pure Ag 2 WO 4 Compared with ZnSnO 3 / Ag 2 WO 4 The arc radius in the EIS spectrum of the composite material is the smallest, indicating that it has the lowest electronic conversion resistance, the highest charge separation efficiency and the best photocatalytic performance. The photocurrent density curve can reflect the separation and migration ability of photogenerated carriers. The transient photocurrent response of the sample under visible light irradiation was measured through 5 on-off intermittent irradiation cycles. Figure 6 As can be seen from (b), in the five consecutive on-off cycles, ZnSnO 3 / Ag 2 WO 4 The transient photocurrent response of ZnSnO 3 / Ag 2 WO 4 The transient photocurrent density of the composite material is significantly higher than that of pure ZnSnO 3 and pure Ag 2 WO 4 , indicating that ZnSnO 3 / Ag 2 WO4 The composite material has the best ability to generate and transport photocarriers. The Mott-Schottky plot was used to further study the ZnSnO 3 / Ag 2 WO 4 The semiconductor type and band structure of the composite material. Figure 6 As shown in (c), the positive slope of the Mott-Schottky curve indicates that they are n-type semiconductors. ZnSnO 3 and Ag 2 WO 4 The flat band potential (Efb) of ZnSnO is –0.23V and 0.51V (relative to Ag / AgCl). For n-type semiconductors, the Efb value is very close to the CB potential, which is –0.23V and 0.51V (relative to Ag / AgCl). According to the potential conversion relationship: E(NHE)=E(Ag / AgCl)+0.197, it is concluded that ZnSnO 3 and Ag 2 WO 4 The CB is –0.03V and 0.71V (relative to NHE). The separation of photogenerated charges is crucial to the photocatalytic activity of semiconductors, and luminescence is caused by the migration, transfer, and recombination of photoluminescent carriers in semiconductors. Therefore, the luminescence spectrum is used to determine the separation efficiency of photogenerated carrier capture and migration separation in semiconductors. Generally speaking, the better the separation and migration efficiency of photoluminescent carriers, the lower the photoluminescence intensity in the luminescence spectrum, indicating that the recombination rate of photoelectron-hole pairs is low and the semiconductor catalyst has a higher photocatalytic activity. Figure 6 (d) shows that pure ZnSnO 3 The luminescence peak intensity is the highest, indicating that the sufficient efficiency of carriers is the highest. 3 / Ag 2 WO 4 The PL emission of the composite is weak, indicating that ZnSnO 3 / Ag 2 WO 4 The composite material has a high photoinduced electron and hole separation efficiency, thus effectively facilitating charge transfer.

[0048] Under visible light irradiation, tetracycline was used as the target pollutant to study the photocatalytic activity of the prepared photocatalyst. In order to improve the accuracy of the experiment, a blank experiment was also carried out. All mixed solutions were stirred for 30 minutes in the dark before irradiation to achieve adsorption-desorption equilibrium. The catalytic effects of different catalysts are shown in Figure 2. Figure 7 As shown in (a), without adding photocatalyst, the concentration of tetracycline solution remains almost unchanged, indicating that tetracycline is relatively stable. 2 WO 4The catalytic activity of the catalyst was not ideal. When exposed to visible light for 15 min, the degradation rate of tetracycline was only 12.14%, which may be due to the presence of Ag. 2 WO 4 The band gap of pure ZnSnO is wide and the response range to visible light is narrow, resulting in low photocatalytic efficiency. 3 The catalytic activity is slightly better than that of pure Ag 2 WO 4 , the degradation rate of tetracycline was 39.03% after 15 min of visible light irradiation. - and h + It is easy to recombine under light conditions, resulting in low photocatalytic activity. 2 WO 4 The composite material showed better catalytic performance. When exposed to visible light for 15 min, the degradation rate of tetracycline was above 45%. 3 / Ag 2 WO 4 The composites showed different degradation rates in the order of ZA-2>ZA-3>ZA-1. Under the same reaction conditions, the degradation rate of ZA-2 reached a maximum of 62.87% when exposed to visible light for 15 min, which was due to the formation of heterojunctions and the increase of catalytic active sites. In addition, all photocatalysts used for photocatalytic degradation of tetracycline conformed to the pseudo-first-order kinetic model:

[0049] ln(C t / C 0 )=–kt

[0050] Where t is the irradiation time, k is the kinetic constant (min -1 ), C 0 is the initial concentration of tetracycline at 0 min, C t is the actual concentration of tetracycline at time t. The kinetic curves of different catalysts are as follows Figure 7 As shown in (b), ZnSnO 3 、Ag 2 WO 4 The k constants of ZA-1, ZA-2 and ZA-3 are 0.02261min -1 、0.00306min -1 、0.028min -1 、0.03739min -1 and 0.02834min -1 The change of reaction rate is consistent with the photocatalytic activity. Among them, ZA-2 has the highest reaction rate. 3 and Ag 2 WO 41.65 times and 12.22 times, indicating that ZnSnO 3 With Ag 2 WO 4 The heterojunction formed between them is conducive to improving the photocatalytic performance. The photostability and reusability of photocatalysts are another important factor affecting their practical application. Under the same experimental conditions, continuous degradation experiments showed that ZnSnO 3 / Ag 2 WO 4 Changes in catalytic performance. Figure 7 As shown in (c), after three cycles, ZnSnO 3 / Ag 2 WO 4 There is no obvious loss in the photodegradation effect of the composite material, indicating that the prepared composite material has stable performance during repeated use and has good application prospects in actual industry.

Claims

1. A method for preparing a photocatalyst for degrading tetracycline, characterized in that: The following steps are involved: S1. Synthesis of ZnSnO3: Dissolve SnCl4·5H2O and NaOH in deionized water, stir evenly, adjust the solution pH to 11.3, heat to 60°C, add ZnSO4·7H2O, and keep at 60°C for at least 8h; the reactants are separated by centrifugation to obtain a solid product, which is washed with deionized water, dried at 60°C for 12h, taken out and calcined at 580°C for 2h to obtain ZnSnO3; Synthesis of S2 and ZA-2: Add Na2WO4·H2O and ZnSnO3 into deionized water and stir to obtain solution A; dissolve AgNO3 in deionized water with a molar ratio of 2:1 to obtain solution B; add solution B into solution A and stir evenly, take out the solid product obtained by the reaction, wash and dry it, and calcine it at 400°C for 2h to obtain the photocatalyst ZnSnO3 / Ag2WO4, called ZA-2.

2. The method for preparing a photocatalyst for degrading tetracycline according to claim 1, characterized in that: The material ratio in step S1 is:

3. The method for preparing a photocatalyst for degrading tetracycline according to claim 1, characterized in that: The material ratio in step S2 is: Na2WO4·H2O ZnSnO3 Deionized water 0.20g 0.56g 80mL.

4. The method for preparing a photocatalyst for degrading tetracycline according to claim 3, characterized in that: The amount of Na2WO4·H2O added in step S2 was increased by 50%, and the photocatalyst ZnSnO3 / Ag2WO4 generated by the reaction was called ZA-1.

5. The method for preparing the photocatalyst for degrading tetracycline according to claim 3, characterized in that: The amount of Na2WO4·H2O added in step S2 was reduced by 50%, and the photocatalyst ZnSnO3 / Ag2WO4 generated by the reaction was called ZA-3.

6. A photocatalyst for degrading tetracycline, characterized in that: The photocatalyst is prepared by the method for preparing the photocatalyst according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method of composite photocatalyst as well as product thereof

    CN103566924A

  • Photocatalyst for degrading doxycycline and preparation method thereof

    CN116803513A

  • G-C3N4-Zn2SnO4 heterojunction photocatalyst as well as preparation method and application thereof

    CN116899610A